2023
DOI: 10.3390/vaccines11020452
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Safety and Immunogenicity of Anti-SARS-CoV-2 Vaccines in Patients with Cirrhosis: A Narrative Review

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causing coronavirus disease 2019 (COVID-19), has led to a pandemic with more than 6.5 million deaths worldwide. Patients with liver cirrhosis (PWLC) are regarded as prone to severe COVID-19. Vaccination against SARS-CoV-2 has been proven to be the most effective measure against COVID-19 and a variety of different vaccines have been approved for use; namely mRNA and vector-based, inactivated, whole virion, and protein subunit vaccines. Unfortunately, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Although several previous studies have shown weakened antibody responses to COVID-19 vaccines in patients with cirrhosis, 35 38 the finding is still controversial 39 Because some studies found no differences in the humoral responses of cirrhotic and noncirrhotic patients. 40 , 41 In this study, the antibody responses in the two groups were similar (data not shown), which may be explained by the small sample size or different vaccine types.…”
Section: Discussionmentioning
confidence: 96%
“…Although several previous studies have shown weakened antibody responses to COVID-19 vaccines in patients with cirrhosis, 35 38 the finding is still controversial 39 Because some studies found no differences in the humoral responses of cirrhotic and noncirrhotic patients. 40 , 41 In this study, the antibody responses in the two groups were similar (data not shown), which may be explained by the small sample size or different vaccine types.…”
Section: Discussionmentioning
confidence: 96%
“…Patients with liver cirrhosis are characterized by immune dysfunction, leading amongst others in defective vaccineresponse [28][29][30] and a high susceptibility in viral and bacterial infections. This, in conjunction with the fact that, most drugs used against SARS-CoV-2 are hepatotoxic and are therefore contra-indicated in severe liver insufficiency, has made liver cirrhosis to be presumed as a significant risk factor for severe COVID-19.…”
Section: Liver Cirrhosismentioning
confidence: 99%
“…The overall benefits of vaccination outweigh the risks of these rare side effects ( Bril et al., 2021 ; Chow et al., 2022 ; Efe et al., 2022 ; Lleo et al., 2022 ; Palla et al., 2022 ). Several studies focusing on the immunogenicity of SARS-CoV-2 vaccination in CLD patients reported that the CLD patients developed a lower protective immune response after two doses of inactivated, mRNA or vector-based SARS-CoV-2 vaccines, compared to healthy individuals ( Ai et al., 2022 ; Bakasis et al., 2022 ; Duengelhoef et al., 2022 ; Ruether et al., 2022 ; Thuluvath et al., 2021 ; Toutoudaki et al., 2023 ; Xiang et al., 2021 ). After two shots of the inactivated vaccine, the seropositivity rates of neutralizing antibodies were higher in CLD patients with Child-Pugh A classification than those with B and C ( Wang et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%